2005
DOI: 10.1093/jnci/dji341
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Postmenopausal Breast Cancer Risk Defined by Estrogen and Progesterone Receptor Status: A Prospective Cohort Study

Abstract: The observed association between risk of developing postmenopausal ER+ breast cancer and alcohol drinking, especially among those women who use postmenopausal hormones, may be important, because the majority of breast tumors among postmenopausal women overexpress ER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
103
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 34 publications
6
103
2
Order By: Relevance
“…Epidemiology relatively high prevalence of exogenous estrogen ever-users ($20-45%), [31][32][33] versus our 11% at baseline. Further investigation of this effect is warranted.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Epidemiology relatively high prevalence of exogenous estrogen ever-users ($20-45%), [31][32][33] versus our 11% at baseline. Further investigation of this effect is warranted.…”
Section: Discussionmentioning
confidence: 74%
“…32,59 Our results for ERþ tumors in overweight women (BMI ! 25) do not support a previous report that the positive association between alcohol consumption and the development of ERþ tumors was confined to women with BMI <25.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…10 Only few studies have specifically addressed a possible interaction between alcohol and hormone use on the risk of breast cancer in large populations. [11][12][13][14] These studies have consistently found the combined effect of alcohol and hormones to be stronger than the effect of either one of them alone. [11][12][13][14] However, in a pooled analysis, the association between alcohol and breast cancer was not modified by hormone use 6 and no interaction between alcohol and hormone use has been reported in several case-control studies.…”
mentioning
confidence: 90%